RATIONAL CHOICE INSTITUTIONALISM, CONSTITUTIONAL REFORM, AND CONSTITUTION MAKER IN INDONESIA - Baidhowah, Adfin Rochmad (Jurnal Politik Pemerintahan Dharma Praja, 2020)
Most political literature argues that outcomes in Indonesian constitutional reform 1999-2002 were determined mainly by the political actors. Notwithstanding the existing research providing insightful evidence, there is still a gap in which those literature discount the role of the party system in shaping and constraining the way the political actors within a party behave. Drawing on one of the new institutionalism concepts – ‘rational choice institutionalism' – the argument puts forth here is that Indonesian multi-party system (independent variable) forced the political parties (intermediary variable) to form a winning-coalition which finally produced a compromised outcome (dependent variable) of constitutional reform on the articles about relations between president and legislature.